THE ROLE OF THE ENGLISH LANGUAGE IN MEDICINE - Nabieva Umida Khusanovna (Western European Studies, 2025)
English is considered the global communication language in the field of modern medicine. Scientific research, international conferences, modern medical technologies and the activities of international organizations are primarily conducted in English.This article provides information about the role of the English language in medicine, its importance on an international scale and its role in the professional development of medical specialists. Knowledge of English opens new opportunities for doctoes and students and unites the healthcare system on a global level.
Keywords: English language; medicine; scientific research